Biosurfactants—a new frontier for social and environmental safety: a mini review. Issue 1 (January 2018) - Akbari, Sweeta; Abdurahman, Nour Hamid; Yunus, Rosli Mohd; Fayaz, Fahim; Alara, Oluwaseun Ruth
Graphical abstract: Abstract: Biosurfactants are amphiphilic compounds synthesized from plants and microorganisms. These compounds are well known to be promising alternative molecules for industrial and domestic applications due to their high biodegradability, low toxicity, multi-functionality, environmental capability, and availability of resources. In recent times, the chemical compounds of biosurfactants have gained much attention because they are considered as a suitable alternative and eco-friendly materials for remediation technology. The current society is facing several challenges of implementation, enforcing environmental protection and climate change for the next generations. Thus, studies on human and environmental safety to improve the efficiency of sustainable technologies on environmental remediation are being investigated. Biosurfactants exhibited an efficient and successful application in various industries such as cosmetic, pharmaceutical, food, petroleum, agricultural, textile, and wastewater treatment. In this regard, this review focused on the advantages of biosurfactants over the synthetic surfactants produced from petroleum-based products along with their potential application in different industries.